Deacetylated Cellulose Acetate/Polyurethane Composite Nanofiber Membranes with Highly Efficient Oil/Water Separation and Excellent Mechanical Properties. Issue 10 (10th July 2021) - Wang, Weiwen; Ma, XiRui; Si, Junhui; Cui, Zhixiang; Wang, Qianting; Liu, Xianhu
Abstract: Nowadays, oil pollution has become more serious, which causes great threats both to the ecological environment and human life. In this study, a novel type of multifunctional deacetylated cellulose acetate/polyurethane (d‐MCA :MTPU ) composite nanofiber membranes for oil/water separation are successfully fabricated by electrospinning, which show super‐amphiphilicity in air, super‐hydrophilicity in oil, and oleophobicity in water. All the d‐MCA :MTPU composite nanofiber membranes with different mass ratios can be used as water‐removing, oil‐removing, and emulsion separation substance only by gravity driving force. The highest separation flux for water and oil reaches up to 37 000 and 74 000 L m −2 h −1, respectively, and all the separation efficiencies are more than 99%. They have outstanding comprehensive mechanics performance, which can be controlled by simply adjusting the mass ratios. They show excellent antifouling and self‐cleaning ability, endowing powerful cyclic stability and reusability. Those results show that d‐MCA :MTPU composite nanofiber membranes have great application prospects in oil/water separation. Abstract : Novel type of multifunctional d‐MCA :MTPU composite nanofiber membranes for oil/water separation are successfully fabricated by electrospinning. They can be used as water‐removing, heavy oil‐removing, and emulsion separation substance under harsh environment only by gravity driving force. They show high separation flux, high separation efficiency, excellent antifouling ability, and outstanding comprehensive mechanical properties, endowing powerful cyclic stability and reusability.